الصفات المحمودة لدى الداعي وعلاقتها بنجاح الدعوة - Armiwati Bt Muhammad Yasin; أرميواتي محمد ياسين (Universiti Sains Islam Malaysia, 2022)
This research will discuss on a da'ie good traits and it relations that contribute to the success of 'dakwah'. The study sought to understand the traits that every da'ie should has and practices in order to ensure the success of 'dakwah' effectively. Furthermore it will classify the good traits according to their differentiation in term to comprehend the society a da'ie himself or her self better. The tool employed for data gathering purpose was the library research, which referred to the books, magazines, journal, and articles that relate to the 'dakwah'. This research will also view the three main behaviors that every should has which comprise the attitude of 'Khuluqiah' 'Ilmiah' and 'Qiadiah'. The da'ie should not merely possess the high moral value but he or she should be a knowledgeable and a quality leadership as well. The finding indicates that the good traits which have been viewed are very important to all the da'ies in order to maintain the victory of their dakwah that base upon the Holy Quran, Hadith, and ulama views. This research will give a benefit and more information on the good traits that every da'ie should own in term to implement and ensure the success of 'dakwah' effectively.